Assessment of Surgery Resident Competency Provided by Patients. Issue 8 (November 2016) - Zhu, Yaxin; Yan, Tingmei; Qu, Bo
Abstract : Abstract: The objective of this study was to assess the competency of surgery residents from the patient perspective in the current healthcare environment in China. The authors performed an assessment of 508 surgery residents in Liaoning province. Seven patients were as a group to complete the self-administered questionnaires on the survey for each individual corresponding resident. A 5-point rating scale with an unable-to-evaluate category was used to assess surgery resident competency by patients. Reliability and validity were assessed by Cronbach alpha (α) and exploratory factor analysis, respectively. Statistical analysis was performed using SPSS 13.0. The surveys on 421 residents were valid, and the valid response rate was 82.8%. A total of 2947 questionnaires from patients were analyzed in this study. The Cronbach α coefficient was 0.92. The 4 factors emerging in the exploratory factor analysis reached a cumulative contribution rate of 66.98%. The items of "promotes health maintenance (talks about preventive care)" (206/7.0%), "tells me about any side effects of the medicine" (177/6.0%), "spends enough time with me" (189/6.4%), and "answers my questions thoroughly" (168/5.7%) were scored <4 by higher percentage of patients. The instrument provided an acceptable means for patients to evaluate the competency of Chinese surgery residents. Surgery residents should improve their competencies on preventive care, patient safety, and communication skills.